Adaptation of muscle coordination to altered task mechanics during steady-state cycling - Neptune, R. R.; Herzog, W. (Journal of Biomechanics, 2000)
The objective of this work was to increase our understanding of how motor patterns are produced during movement tasks by quantifying adaptations in muscle coordination in response to altered task mechanics. We used pedaling as our movement paradigm because it is a constrained cyclical movement that allows for a controlled investigation of test conditions such as movement speed and effort. Altered task mechanics were introduced using an elliptical chainring. The kinematics of the crank were changed from a relatively constant angular velocity using a circular chainring to a widely varying angular velocity using an elliptical chainring. Kinetic, kinematic and muscle activity data were collected from eight competitive cyclists using three different chainrings — one circular and two different orientations of an elliptical chainring. We tested the hypotheses that muscle coordination patterns (EMG timing and magnitude), specifically the regions of active muscle force production, would shift towards regions in the crank cycle in which the crank angular velocity, and hence muscle contraction speeds, were favorable to produce muscle power as defined by the skeletal muscle power-velocity relationship. The results showed that our hypothesis with regards to timing was not supported. Although there were statistically significant shifts in muscle timing, the shifts were minor in absolute terms and appeared to be the result of the muscles accounting for the activation dynamics associated with muscle force development (i.e. the delay in muscle force rise and decay). But, significant changes in the magnitude of muscle EMG during regions of slow crank angular velocity for the tibialis anterior and rectus femoris were observed. Thus, the nervous system used adaptations to the muscle EMG magnitude, rather than the timing, to adapt to the altered task mechanics. The results also suggested that cyclists might work on the descending limb of the power-velocity relationship when pedaling at 90 rpm and sub-maximal power output. This finding might have important implications for preferred pedaling rate selection.